Successful treatment of intussusception by hydrostatic reduction in pediatric patients: Is everything okay? - Beger, Burhan (Journal of Surgery and Medicine, 2018)
Aim: Intussusception, which is defined as telescopic insertion of proximal bowel segment into distal bowel segment, can be cured completely with surgical intervention. Intussusception can be successfully treated by ultrasound guided hydrostatic reduction (USGHR) if there is no necrosis or perforations of intestines. However, misdiagnosing or omitting secondary conditions which can be seen together with intussusception leads to an inevitable rise in morbidity. In this study, we would like to present a retrospective review of the intussusception patients which developed complications due to misdiagnosis within a pediatric surgery clinic in terms of diagnosis and treatment. Methods: 12 patients who were treated for intussusception using USGHR between May 2014 and September 2017 in Van Yuzuncu Yil University Faculty of Medicine Pediatric Surgery Department were retrospectively reviewed for missed conditions and coincidental pathologies. The data about these case series such as age, sex, patient symptoms, diagnosis and treatment methods, complications and hospitalization periods were evaluated. Results: 12 (5 Female – 7 Male) patients, who were diagnosed with invagination with complaints of abdominal pain, refractory emesis, crying attacks, bloody stool and abdominal distension that treated with USGHR with a mean age of 34 (Range 6 – 98) months, showed a worse clinical prognosis due to missed secondary conditions. Missed secondary pathologies included appendicitis (3 cases), lymphoma (1 case), Meckel diverticulitis (1 case), appendiceal intussusception (3 cases), acute gastroenteritis (3 cases) and Henoch-Schonlein Purpura (1 case). The patient with Henoch-Schonlein purpura diagnosis was treated with USGHR in combination with corticosteroids and all the other cases required open surgery. Follow-up of the patient with Henoch-Schonlein purpura is ongoing whereas all the other cases were treated successfully. Conclusion: Although most intussusception cases are successfully treated with non-surgical USGHR treatments in our pediatric surgery clinic, missing the conditions that are seen with invagination causes an increase in surgical intervention rates, morbidity rates and medical costs. The main challenge for pediatric surgeons in invagination cases caused by pathological leading point conditions is the possibility of missing the actual underlying disease which caused the invagination following a successful USGHR after target-sign is detected. Although ultrasound and computed tomography studies might be helpful in preliminary diagnosis, it must be kept in mind that an actual diagnosis can only be done with surgery in some cases.